2009
DOI: 10.1016/j.ejpoleco.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Growing apart? A tale of two republics: Estonia and Georgia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The economy, foreign investments and trade grew rapidly (World Bank, 2008). Compared to the conditions in other post-socialist countries, Estonia has therefore often been characterized as a 'success story' (Panagiotou, 2001;Lauristin, 2003;Gylfason and Hochreiter, 2009). This success is further emphasized by Estonia's inclusion in the European Union in 2004 and the Euro zone in 2011 (European Commission, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The economy, foreign investments and trade grew rapidly (World Bank, 2008). Compared to the conditions in other post-socialist countries, Estonia has therefore often been characterized as a 'success story' (Panagiotou, 2001;Lauristin, 2003;Gylfason and Hochreiter, 2009). This success is further emphasized by Estonia's inclusion in the European Union in 2004 and the Euro zone in 2011 (European Commission, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, inter-governmental co-operation and negotiations accelerate international trade and growth. In this regard, Gylfason and Hochreiter (2009) showed a study where a comparison of the economic performance between the Republic of Estonia and Georgia since the collapse of 1991. Most of the findings showed that smart governance, institutional reforms, and enhancements within the instructional system play an important role in raising output.…”
Section: Review Of Relevant Literaturesmentioning
confidence: 99%
“…To some extent, the enabling business environment reflected close proximity to the EU markets and strong incentives of the EU accession that country benefited from. 20 As Gylfason and Hochreiter (2009) write, for Estonia "…the prospect of rapid EU integration, the EU perspective, provided a critical anchor for sustained political, institutional, and economic reforms across the political spectrum. "…”
Section: Annex I Country Examples -Contrasting Experiences Of Estonia and Belarusmentioning
confidence: 99%